Numerical Investigation on Aerodynamic Performances of the Single-Stage Transonic Turbine With Various Coolant Ejection Positions and Coolant Mass Flow Rates - Zhang, Jinming; Zhou, Xun; Du, Wei; Xu, Senpei (Frontiers in Energy Research, 2022)
The effects of film cooling holes on the suction surface and the coolant mass flow were studied in this paper, which focused on the load distribution and flow characteristics such as shock migration. A high and low degree of reaction scheme (degree of reaction=0.3, 0.53) is selected to investigate numerically aerodynamic performance with consideration of air film cooling. The results show above factors have different influences on the intensity and the trailing edge shock direction. The reflected shock weakens and then recovers when the coolant ejection position approaches and departs from the reflection point. Altering coolant ejection position or coolant mass flow rate mainly affects the load at the front and middle of the blade and has some effects on the pressure rise at the trailing edge too. There is an optimal position (x/Cax=0.6) and an optimal coolant volume (150% mainstream mass flow rate) for flattening pressure rise and weakening shocks, thus reducing losses.